Characterization of a nuclear transport factor 2-like domain-containing protein in Plasmodium berghei - Mamoru Niikura; Toshiyuki Fukutomi; Jiro Mitobe; Fumie Kobayashi (Malaria Journal, 2024)
Abstract Background Plasmodium lacks an mRNA export receptor ortholog, such as yeast Mex67. Yeast Mex67 contains a nuclear transport factor 2 (NTF2)-like domain, suggesting that NTF2-like domain-containing proteins might be associated with mRNA export in Plasmodium. In this study, the relationship between mRNA export and an NTF2-like domain-containing protein, PBANKA_1019700, was investigated using the ANKA strain of rodent malaria parasite Plasmodium berghei. Methods The deletion mutant Δ1019700 was generated by introducing gene-targeting vectors into the P. berghei ANKA genome, and parasite growth and virulence were examined. To investigate whether PBANKA_1019700 is involved in mRNA export, live-cell fluorescence imaging and immunoprecipitation coupled to mass spectrometry (IP-MS) were performed using transgenic parasites expressing fusion proteins (1019700::mCherry). Results Deletion of PBANKA_1019700 affected the sexual phase but not the asexual phase of malaria parasites. Live-cell fluorescence imaging showed that PBANKA_1019700 localizes to the cytoplasm. Moreover, IP-MS analysis of 1019700::mCherry indicated that PBANKA_1019700 interacts with ubiquitin-related proteins but not nuclear proteins. Conclusions PBANKA_1019700 is a noncanonical NTF2-like superfamily protein.